Le texte théâtral et l’autotraduction dans le contexte minoritaire de l’Ouest du Canada - Czubińska, Małgorzata (2023)
In the last 30 years there has been an increased interest among researchers in the problem of self-translation, particularly in the context of novel translation. The aim of the following paper is to present the challenges of self-translation in a context of dramatic texts. The corpus of analysis for this article will be three plays written by bilingual artists who are rooted in Western Canadian provinces – Saskatchewan and Manitoba. The analysis of the fragments of the originals compared with the self-translated versions of the plays: "La Trahison/The Betrayal" by Laurier Gareau (2004) "La Maculée/sTain" by Madeleine Blais-Dahlem (2012) and Marc Prescott's "Fort Mac" (2009) will allow us to determine the characteristics of self-translation of each of these "privileged translators".
Keywords: self-translation; translation of drama; bilingualism; French Canadian literature; orality in translation